Assessment for Learning and Feedback in Chemistry: A Case for Employing Information and Communication Technology Tools - Opateye, Johnson; Ewim, Daniel Rapahael Ejike (Universitas Terbuka, 2021)
Assessment is essential in the learning and teaching process. In chemistry teaching, deployment of assessment to ascertain the levels of assimilation and understanding of concepts being taught in the class is considered central in the learning process. Through the assessment for learning, teachers check students’ understanding and get valuable feedback data on students’ learning. This data is used to modify and improve instruction. Educational world order has drastically changed due to the emergency of COVID-19 that influenced the modes of educational delivery at such a time like this. The only option to deliver learning and assessment processes is the deployment of technology to be able to meet the demands of pandemic and its associational protocols. Information and Communication Technology (ICT) affects every facet of life including education. This paper, therefore, examined the nature of assessment of chemistry learning and the ICT tools that are required to drive the assessment procedures. In addition, it discussed the ICT feedback mechanisms in assessing the learning process in chemistry. Consequently, the paper suggested that relevant ICT tools should be used by chemistry teachers to monitor students’ academic progress and foster ICT-driven effective feedback for assessment of chemistry learning. As a result, ICT should be deployed to assist chemistry teachers in carrying out assessment for learning to diagnose learners’ understanding and difficulties during the process of instruction.